PENCATATAN PERKAWINAN DALAM MULTI PERSPEKTIF - Muhammad Romli Muar (Fakultas Syariah - IAI Al-Qolam Malang, 2021)
Nowadays, marriage registration is a compulsory in almost all parts of the world, including in countries with Muslim populations. However, marriage registration is not regulated in the classical fiqh tradition, although scholars differ on the position of marriage registration. Viewed from the side of maslahah, marriage registration contains great benefits or goodness in marital life. The practice of registering marriages in various Muslim-populated countries shows that there are differences in the position of the registration. Some are only administrative in nature, and some make registration as one of the requirements for the validity of marriages.